The Role of Thrombolysis in the Complex Treatment of Complicated Popliteal Artery Aneurysms - I. P. Mikhailov; L. S. Kokov; V. N. Lavrenov (Неотложная медицинская помощь)
RELEVANCE Thrombosis of a popliteal artery aneurysm is an intractable problem. For decades, the number of amputations in this disease has remained at the level of 20% and does not have a significant downward trend due to the fact that during thrombosis of an aneurysm, the infragenicular arteries, the only “outflow paths” for bypass surgery, are also thrombosed. Currently, in order to increase the capacity of the peripheral bloodstream, thrombolytic therapy has been proposed.AIM To evaluate the effectiveness of preoperative and intraoperative thrombolytic therapy in the surgical treatment of thrombosed popliteal aneurysms.MATERIAL AND METHODS In the period from 1997 to 2020, 94 patients with acute ischemia of the lower extremities caused by thrombosed popliteal aneurysms underwent 98 reconstructive surgeries at the N.V. Sklifosovsky Research Institute for Emergency Medicine. The age of the patients was 62.5±10.1 years. Group I (n=66/98 patients, 67.3%) consisted of patients after primary reconstructive surgery; Group II (n=32/98, 32.7%) consisted of patients who, in order to improve the patency of the infragenicular arteries, underwent thrombolytic therapy in addition to surgery (12 preoperative catheter-directed, 20 intraoperative). A retrospective analysis was carried out.RESULTS Limb preservation was achieved in 86.7% of patients. In Group I, early postoperative thrombosis occurred in 22.7% of cases (n=13/98), in Group II — in 6.3% (n=2/32), p<0.05; amputations were performed in Group I in 18.1% of patients (n=12/66), in Group II — in 3.1% of patients (n=1/32), p<0.04.